Allium sulaimanicum: A new Allium species and section from Pakistan - Khan, Nazar; Friesen, Nikolai; Sultan, Amir; Fritsch, Reinhard M.; Khan, Tahir; Ishaq, Kamran (Frontiers in Plant Science, 2022)
A new species Allium sulaimanicum is described from northern Balochistan and southern Khyper Pakhtunkhwa in Pakistan based on morphological, molecular and cytological studies. The new species is characterised by long runner-like cylindrical rhizomes of adult plants, cylindrical bulbs, linear leaves with minute soft hairs along veins, campanulate perigonium, white to creamy white, ovate to elliptical, 4.5-5 mm long tepals, acute, recurved at apex, with brownish to purplish nerves, filaments as long as to slightly longer than tepals, inner filaments slightly more dilated than outer at base, yellow to brick red anthers, hexagonal ovary, white and papillate/warty along angles, style 2-5 mm, the simple to slightly capitate stigma is sometime exserted. The presence of long herbaceous rhizome indicated serious isolation of the new species hence, a new section Sulaimanicum is proposed to accommodate the new species. The new species is diploid with a chromosome number of 2n =16. Detailed morphological description, illustrations, phylogenetic analyses based on sequences of plastid spacers (rpl32-trnL (UAG) and trnQ-rps16) and nuclear ITS, karyotype features and a distribution map of the new species are provided.